Physicians’ experience with follow-up care of childhood cancer survivors – challenges and needs (Swiss Medical Weekly, 2017)
BACKGROUND Regular follow-up care is essential for childhood cancer survivors, but we know little about physicians’ experience with it. We aimed to describe: (1) involvement of Swiss physicians in follow-up care; (2) content of follow-up care provided; (3) problems encountered; and (4) additional resources needed. ​ MATERIALS AND METHODS: Within this cross-sectional survey we sent adapted questionnaires via professional associations to a sample of medical oncologists (MOs), paediatric oncologists (POs), general practitioners (GPs) and paediatricians (P) in Switzerland. Only oncologists involved in follow-up care were asked to report problems. GPs and Ps not involved in follow-up could indicate why. All physicians were asked about the content of follow-up care provided and additional resources needed. RESULTS A total of 183 physicians responded (27 MO, 13 PO, 122 GP, 21 P). Involved in follow-up were 81% of MOs, 85% of POs, 39% of GPs and 81% of Ps. Follow-up content differed between oncologists (MO and PO) and generalists (GP and P), with generalists examining or informing less in regard to the former cancer. POs reported more problems than MOs: many POs reported problems with transition of survivors to adult care (91%), and because of financial resources (73%) and time restraints (73%). MOs reported most problems during transition (23%). Not being aware of a survivor was the most common reason for GPs and Ps not participating in follow-up (74%). All groups reported a need for standardised protocols (85–91%) and specialised training (55–73%). GPs (94%) and Ps (100%) additionally desired more support from oncologists. CONCLUSIONS To improve quality and efficiency of follow-up care a national follow-up care model including standardised protocols and guidelines needs to be developed.